THE EFFECT OF ACCOUNTING INFORMATION SYSTEMS, TRANSPARENCY AND ACCOUNTABILITY ON CORPORATE FINANCIAL PERFORMANCE - Andianti, Diah Ayu; Afiqoh, Nyimas Wardatul (Antis-Publisher, 2024)
In the evolving landscape of corporate finance, the role of Accounting Information Systems (AIS), transparency, and accountability in influencing financial performance remains a critical area of investigation. Despite the extensive literature on AIS, transparency, and accountability, there is limited empirical evidence on their direct impact on financial performance within contemporary organizational contexts. Previous studies have often overlooked the nuanced effects of these variables on financial outcomes, particularly in diverse organizational settings. This study aims to elucidate the relationship between AIS, transparency, and accountability, and their combined effect on financial performance, using agency theory and Technology Acceptance Model (TAM) theory as analytical frameworks. Data collected from 50 employees across various divisions via social media questionnaires were analyzed using multiple linear regression. The analysis revealed that AIS did not significantly impact financial performance, whereas transparency and accountability exhibited a positive and significant relationship with financial performance. This study contributes to the literature by demonstrating the differential impact of transparency and accountability versus AIS on financial performance, highlighting the need for a refined focus on transparency and accountability practices. The findings underscore the importance of enhancing transparency and accountability mechanisms to better align with corporate financial performance objectives. This research provides valuable insights for policymakers and corporate managers aiming to optimize financial outcomes through improved organizational practices.